Repair of the Starter Motor Unit of the 966 F Series II Cat Wheel Loader at the Ola Workshop in Nunukan Regency - Al Amin; Ismail Ramli; Lisa Binti Harun; Halman Halman (Jurnal Impresi Indonesia, 2025)
The starter system in heavy equipment plays a crucial role in initiating engine operation by converting electrical energy from the battery into mechanical energy through a direct current (DC) motor. This study focuses on the repair and troubleshooting process of the motor starter in the Caterpillar Wheel Loader 966 F Series II, which experienced engine-starting failure at the Ola Workshop, Nunukan Regency. The research aimed to identify the causes of malfunction and to determine the appropriate repair method to restore normal engine operation. The data collection methods included field observation, interviews with mechanics, and documentation. The results revealed that the failure was primarily caused by worn carbon brushes, with brush length reduced to less than the standard 10 mm, resulting in an interruption of electric current flow to the armature. To resolve this issue, the damaged carbon brushes were replaced with new ones of standard specification (10 mm). After replacement, the motor starter functioned properly, allowing the engine to start efficiently and operate normally. The study highlights the importance of preventive maintenance and periodic inspection of electrical components in heavy equipment to prevent downtime and maintain operational reliability. This research contributes to the practical understanding of motor starter repair procedures, particularly for wheel loaders operating in field conditions with high mechanical and environmental stress.